2017
DOI: 10.1534/genetics.117.203067
|View full text |Cite
|
Sign up to set email alerts
|

Model Organisms Facilitate Rare Disease Diagnosis and Therapeutic Research

Abstract: Efforts to identify the genetic underpinnings of rare undiagnosed diseases increasingly involve the use of next-generation sequencing and comparative genomic hybridization methods. These efforts are limited by a lack of knowledge regarding gene function, and an inability to predict the impact of genetic variation on the encoded protein function. Diagnostic challenges posed by undiagnosed diseases have solutions in model organism research, which provides a wealth of detailed biological information. Model organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(157 citation statements)
references
References 156 publications
2
153
0
Order By: Relevance
“…As whole-exome (WES) and whole-genome sequencing (WGS) become part of the general medical practice in the era of personalized medicine (Posey et al, 2019), the number of variants of unknown significance (VUS) in NOTCH and related genes will likely increase at a rapid pace. Understanding the precise mechanism of how each mutation affects protein function is critical since different therapeutic strategies may need to be used based on the specific type of variant an individual carries (Bellen, Wangler, & Yamamoto, 2019;Harnish, Deal, Chao, Wangler, & Yamamoto, 2019;Wangler et al, 2017).…”
Section: Variants and Mutati On S In Human Notch G Ene S That Are Lmentioning
confidence: 99%
“…As whole-exome (WES) and whole-genome sequencing (WGS) become part of the general medical practice in the era of personalized medicine (Posey et al, 2019), the number of variants of unknown significance (VUS) in NOTCH and related genes will likely increase at a rapid pace. Understanding the precise mechanism of how each mutation affects protein function is critical since different therapeutic strategies may need to be used based on the specific type of variant an individual carries (Bellen, Wangler, & Yamamoto, 2019;Harnish, Deal, Chao, Wangler, & Yamamoto, 2019;Wangler et al, 2017).…”
Section: Variants and Mutati On S In Human Notch G Ene S That Are Lmentioning
confidence: 99%
“…Rbcn-3B, which produced a Category A phenotype, encodes a protein involved in Notch signaling during oogenesis through its role in endocytic trafficking and lysosomal function (YAN et al 2009). Coq8, which produced a Category A phenotype, encodes a mitochondrial inner membrane protein that is predicted to be involved in electron transport (ZHU et al 2017) In contrast, many of the genes we identified, including Usp16-45 which is predicted to encode an ubiquitin specific protease, have not been extensively characterized in vivo and it is likely that these proteins also have additional functions as most genes are pleiotropic (WANGLER et al 2017b). These results indicate that screening for the GFP-SKL peroxisomal marker is an effective method to identify new genes that can impact peroxisome dynamics or morphology.…”
Section: Identification Of Genes Involved In Peroxisomal Dynamicsmentioning
confidence: 96%
“…Notable areas in which Drosophila models are having an impact include a wide variety of neurological diseases [reviews include (Okray and Hassan 2013;Coll-Tane et al 2019)]; cancer (Sonoshita and Cagan 2017); metabolic disease and diabetes (Park et al 2014); responses to infection by human pathogens (Apidianakis and Rahme 2011); immune disorders (Bergman et al 2017); heart disease (Viswanathan et al 2014); and inherited disorders (Wangler et al 2017;Mishra-Gorur et al 2019). Drosophila is also increasingly being used to help identify causative variants associated with previously undiagnosed genetic disorders (Wangler et al 2017;Splinter et al 2018). Despite the impressive set of tools currently available for Drosophila genetic studies, locating and/or generating disease models in Drosophila can be time consuming, and at the start of our project, wellcharacterized loss-of-function alleles or validated RNAi and/or sgRNA strains were not available.…”
Section: Introductionmentioning
confidence: 99%